INVESTIGASI KOROSI PIPA FLOWLINE CARBON STEEL PADA SISTEM PRODUKSI MIGAS DAN PENERAPAN SOLUSI PROTEKTIF - Setyani, Atik; Jheno Sheva Hermawan, Moch. Aditya; Prabowo, Imam; Amin, Nur (Universitas Majalengka, 2025)
Corrosion in flowline pipes represents one of the critical challenges frequently encountered in the oil and gas industry, particularly within fluid transportation systems in the upstream sector. This issue significantly compromises material performance, incurs substantial economic losses, and poses serious occupational safety risks. Carbon steel, commonly used in flowline pipes, is highly susceptible to corrosion due to exposure to aggressive environments, including high humidity, formation water, and corrosive gases such as H₂S and CO₂. In line with the growing demands for infrastructure reliability and compliance with safety standards, effective corrosion mitigation has become increasingly urgent. The degradation of pipe integrity due to corrosion can jeopardize the long-term reliability of fluid transport systems, potentially leading to severe operational disruptions and escalating maintenance costs. This study aims to investigate the primary causes of corrosion and evaluate the effectiveness of applied mitigation strategies on flowline pipes at a production facility. The methods examined include the application of protective surface coatings and the use of wrapping systems to inhibit direct contact between the metal and corrosive agents. Additionally, pipe wall thickness measurements were conducted to estimate the remaining service life of the flowline system based on the extent of corrosion-induced degradation. The findings of this study are expected to offer technically sound and practically applicable recommendations for corrosion control, thereby enhancing operational reliability and contributing to the sustainable performance of oil and gas infrastructure.